When a Dollar is Not a Dollar: Examining How Timing and Delivery of Government Transfers Influence Household Consumption Decisions - LaMothe, Ethan G.; Marshall, Mary E.; Schwebke, Jason M. (The Accounting Review, 2026)
ABSTRACT Governments implement wealth transfers with different policy goals and distribution methods. Prior research examines the timing (lump sum/periodic) of transfers but fails to simultaneously consider payment delivery method (standalone/combined with other income). Based on the behavioral life-cycle model, we predict payment timing influences how recipients spend government transfers, but that this effect is muted when the transfer payment is combined with other income. In contrast to prior research, our experimental findings provide theory-consistent results and suggest recipients of a periodic transfer spend more of the transfer than recipients of a lump sum transfer, but only when the transfer is standalone and not combined. Our findings help to explain theory-inconsistent results of prior research and extend the literature on the behavioral life-cycle model and mental budgeting. Moreover, our results suggest policymakers can intentionally structure the distribution of government transfers to encourage household spending or saving consistent with policy goals.